ﻗواﻋد اﻷھﻠﯾﺔ ﻓﻲ اﻟﺗّﻘﻧﯾن اﻟﻣدﻧﻲ وﺗﻘﻧﯾن اﻷﺳرة، ﻣن ﻓرﺿﯾﺔ اﻟﺗﻛﺎﻣل ﺑﯾن اﻟﻧّﺻوص إﻟﻰ واﻗﻊ - Chihani, Samir; Gattal, Hamza (Revue des Sciences Humaines, 2025)
It is known that the civil codification is the general Shariah, reffering to it whenever there is no text on a specific issue in the rest of the relevant laws. Among these laws; the codification of the family. The civil codification included general provisions regarding capacity rules, some of them reffered to the texts of the family codification which had not yet been issued, and this embodies in the phenomenon of the principle of complementarity between the two laws. However, the issuance of the family codification nine years after the issuance of the civil codification showed the converse in many placements. Particularly in the rules governing the capacity of persons; therefore, the purpose of this study was to analyze the content of those rules, with shedding light the areas of incompatibility between them, and then providing solutions to get out of the state of incoherency between texts or even conflict between them.

The Extent of Social Responsibility among Libyan and Palestinian Telecom Companies in Mitigating the Effects of the COVID-19 Pandemic - Rashwan, Abdelrahman; Amarif, Suad (Jordan Journal of Applied Science-Humanities Series, 2024)
This study primarily aims to identify the social responsibility of Libyan and Palestinian telecommunications companies and their contributions to addressing the negative effects resulting from COVID-19. The study focuses on the companies’ efforts to alleviate the burden on the state and citizens, exploring the most significant social contributions made by these companies in response to the pandemic. To answer the research questions and test the hypotheses, the researchers employed a descriptive and analytical approach. After obtaining the necessary data, a validated and evaluated questionnaire was distributed to a sample of 53 individuals, including financial managers, internal auditors, financial analysts, and accountants working in Libyan and Palestinian telecommunications companies. The results of the study indicated that Libyan telecom companies did not contribute significantly to mitigating the negative effects of COVID-19 by activating their social responsibility roles. This conclusion is supported by the respondents' answers, which reflected a moderate degree of contribution, with a mean value of 3.08 and a relative weight of 61.69%, along with a standard deviation of 0.85 and a significance level (Sig) of 0.686. Similarly, Palestinian telecom companies also did not significantly contribute to mitigating the negative effects of the COVID-19 pandemic through their social responsibility roles. Respondents’ answers indicated a moderate level of contribution, with a mean value of 3.24, a relative weight of 64.85%, a standard deviation of 0.849, and a significance level (Sig) of 0.256. The study recommends that Libyan and Palestinian telecommunications companies should enhance their social roles in mitigating the negative effects of the COVID-19 pandemic by actively implementing social responsibility initiatives.
Keywords: COVID-19 Pandemic; CSR; Corporate Communications; Corporate Social Responsibility; Libya; Telecom Company

التحكيم وفقًا لاتفاقية الأمم المتحدة بشأن نقل البضائع عن طريق البحر (هامبورغ، 1978) - Ghassan, ali; Haidara, jaber (Tishreen University journal of research and scientific studies -economic and legal sciences, 2024)
International maritime transport represents the backbone of international trade in our current era, for many reasons, such as low costs and the ability to transport large quantities of goods at once. The United Nations Convention on the Maritime Transport of Goods of 1978, known as the Hamburg Convention, represents a qualitative shift in regulating the rules of maritime transport of goods. Among the important topics regulated by the agreement is the subject of arbitration, as it is the most important means of settling disputes related to international trade contracts, especially the contract for the maritime carriage of goods. Accordingly, this research studies the rules of the Hamburg Convention related to arbitration as a means of settling disputes related to the contract for the maritime carriage of goods. يمثل النقل البحري الدولي عصب التجارة الدولية في عصرنا الحالي، ألسباب عديدة كانخفاض التكاليف والقدرة عمى والمعروفة 1978 نقل كميات كبيرة من البضائع دفعة واحدة، وتمثل اتفاقية األمم المتحدة لمنقل البحري لمبضائع لعام ىامبورغ، نقمة نوعية عمى صعيد تنظيم قواعد النقل البحري لمبضائع، ومن بين الموضوعات اليامة التي باسم اتفاقية نظمتيا االتفاقية، موضوع التحكيم، باعتباره أىم وسائل تسوية النزاعات المرتبطة بعقود التجارة الدولية، وخاصة عقد د اتفاقية ىامبورغ المتعمقة بالتحكيم كوسيمة لتسوية النزاعات النقل البحري لمبضائع، وبناء عميو يتناول ىذا البحث قواع ال
Keywords: Arbitration; Bill of lading; Bills of lading; Carriage of Goods by Sea (1978); Hamburg Convention; Hamburg Rules; International commercial arbitration; Maritime carriage contract; Maritime transport; UN Convention; اتفاقية ىامبورغ; التحكيم; سند الشحن; عقد النقل البحري

The Position of General Principles of Law in the Interpretation of Treaties - Hajjar, Mahmoud; Zamani, Seyed Ghasem (Public Law Researsh, 2023)
The interpretation of treaties is particularly important in the field of treaty law, as in most cases it is not possible to apply treaties without their interpretation. In addition to the text and context of the treaty, the relevant rules of international law, including the general principles of law, can play an important role in the interpretation of treaties. A treaty is a creation of the international legal system, and its interpretation and implementation should be carried out within the context of the legal system that governs it. The main question to which this research intends to answer is: What is the position of general principles of law in the interpretation of treaties? It seems that the use of general principles of law in the interpretation of treaties can reduce the potential fragmentation of international law and promote its coherence. In this research, by using library sources, international documents and international judicial decisions and arbitration awards and using a descriptive-analytical method, the position of general principles of law in the interpretation of treaties will be examined.
Keywords: Article 31 (3) (C) of the Convention of the Law of Treaties; General Principles of Law; International Jurisprudence; Interpretation of Treaties; Systemic Integration

The legal Nature of the Virtual Currency: In-Depth Legal Insight - Al-Majali, Ahmed (UAEU Law Journal, 2023)

Preemption in Shares - Al-Rashidi, Hussein (UAEU Law Journal, 2023)
The Court of Appeals was presented with a dispute concerning the recovery of shares sold. The shareholder of a simplified joint-stock company had invoked the right of preemption, which is established by the Civil Code. The Court decided (on 1/10/2017, Appeals Nos. 1704, 1783/2017, Commercial, Civil, Governmental, Unpublished) that the shareholder could return the sold shares in accordance with his right of preemption. It considered that Company Law did not regulate the restitution of shares in the joint-stock company and that it was, therefore, necessary to refer to the provisions of the Civil Code. We think the decision of the Court of Appeals is subject to criticism. Firstly, even though the legislator does not regulate the restitution of the shares of the holding company, he refers to the regime applicable to the company from which the holding company takes its form. In this case, the holding company took the form of a joint-stock company, whose legislator had organized the shareholder's right to recover the shares offered for sale. Secondly, the Court did not follow the order of the official sources of the legal rule governing companies, namely company law, commercial law and commercial customs. Thirdly, the subject matter of the right of preemption is a real and undivided right, which is not the case for the share, since it is a personal right.

The Extent to which a Contract may be Terminated Based on a Prior Breach of the Contractual Obligation: A Comparative Study - Adwan, Mohdkhair; Otoum, Naim (UAEU Law Journal, 2023)
The Contractual Obligation is proven to be owed by its owner as soon as the contract is concluded or the deadline for its implementation is due, Following this that the contractual violation should be before it not after, and if that kind of violation is the ordinary kind of contractual fault so the happening of contractual violation before the execution is a case been put by rules and Judicial Pronouncements as putting it in certain ordered law firm has its special private rules and obligations that distinguishes it from any similar cases of the expiry of contract. And for that the advanced breaching by any behavior came out of the debtor in a clear or hidden way makes it Impossible or in-vain to execute a future commitment, because of that there will be a serious average on the creditor that that allows him to revoke the contract or ending it or asking for the compensation of any average might be caused by the debtor. The Arabic laws haven’t exclusive a special law for that hidden violation regardless how important it is, and amongst the warnings of going to the ordinary law of handling the wrongs of contractual violations specially with the hidden contractual commitments regarding the typical dissonance with the normal known violation.

Criteria for Considering the Shari’a Need when Applied to a Commercial Insurance Contract: An Applied Jurisprudential Study - Al-Shafei, Ahmed (UAEU Law Journal, 2023)
control and measure it. By proposing a list of criteria used in assessing their existence, consideration or elimination, and to test the criteria, the researcher applied them to a commercial insurance. In order to achieve the goal of the research; the researcher used the inductive analytical method, by following the rules suggested by the Fuqaha’, which required an analysis of some Fuqaha’ sayings, to build standards. The research concluded that the «Need» that some Fuqaha’ considered in the permissibility of commercial insurance does not meet these criteria in a way that supports their opinion. Accordingly; Commercial insurance in its current form is not permissible, which is the opinion of the majority of contemporary Fuqaha’. The research recommends calibration what accepts calibration from the fundamentalist tools, which enable the mujtahid and the researcher to stand on the Shari’a ruling in a disciplined manner, and reduce the difference between the mujtahidin’s considerations of the tools and methods of ruling making.

The Pros and Cons of Third Party Funding in the International Investment Arbitration Regime - Mirveisi, Alireza; Zakerian Amiri, Mehdi; Abdollah Zadeh, Mohammad Ali (Public Law Researsh, 2023)
There is a growing stream of critics who see investment arbitration in favor of foreign investors and as a negative force as opposed to sustainable development. The phenomenon of third-party funding and its use in investment arbitration has increased such concerns. Third-party funding is basically the payment of all or a part of the arbitration costs of one of the parties of dispute by a third party funder which in return, the funder receives a percentage of the output of the award if successful. The purpose of this article is to explain and analyze the theoretical differences between pros and cons of third-party funding regarding the access to justice, screening mechanism for the claims, and the financial consequences on the host state. In this article, the advocates see third-party funding as a means of access to justice for aggrieved investors in investment claims, while the adversaries refering on the profitability of third-party funding, see this method in arbitration a form of wealth transfer from public sector to private corporations and also refer to the asymmetric structure of the investment arbitration regime as well as the risks arising from the transfer of management and control of arbitration process to the third party funders. یک جریان رو به رشدی از منتقدان وجود دارد که داوری سرمایه‌گذاری را به نفع سرمایه‌گذاران خارجی و بعنوان یک نیروی منفی در تضاد با توسعه پایدار می‌داند. پدیده تأمین مالی ثالث و بکارگیری آن در داوری سرمایه‌گذاری به این نگرانی‌ها افزوده است. تأمین مالی ثالث اساساً پرداخت تمام یا بخشی از هزینه‌های داوری یکی از طرفین دعوی توسط تأمین کننده شخص ثالث است که در ازای آن، تأمین کننده مالی درصدی از رأی صادره را در صورت پیروزی دریافت می‌نماید. هدف مقاله، تشریح و تحلیل اختلافات نظری موافقان و مخالفان تأمین مالی ثالث در خصوص دستیابی به عدالت، غربالگری دعاوی و تبعات مالی آن بر دولت است. در این مقاله موافقان، تأمین مالی ثالث را ابزاری جهت دستیابی به عدالت برای سرمایه‌گذاران زیان‌دیده در دعاوی سرمایه‌گذاری در نظر می‌گیرند در حالی که مخالفان با اتکا به اهداف سودآوری تأمین مالی ثالث، این روش را در داوری نوعی انتقال ثروت از بخش عمومی به بخش خصوصی می‌دانند و به ساختار نامتقارن رژیم داوری سرمایه‌گذاری و خطرات ناشی از انتقال مدیریت و کنترل فرایند داوری به تأمین کنندگان شخص ثالث نیز اشاره می‌نمایند.
Keywords: ACCESS TO JUSTICE; Arbitrage; Arbitragem; Arbitration; Investment Arbitration Regime; Investments; Screening Mechanism for Claims; Third Party Funding; تأمین مالی ثالث; دستیابی به عدالت; رژیم داوری سرمایه‌گذاری; غربالگری دعاوی

The Unilateral Arbitration Clause between Permissibility and Nullity - Mahmoud Jaradat, Nashat; JassimSarhan, Ghassan (Information Sciences Letters, 2022)
Researching the judicial applications of Arab countries to one of the issues that have occupied legal thoughts in the Western world for decades and still in one form or another, the so-called Unilateral Arbitration Clauses, we did not find a discussion of the applicability of this clause within the laws. Even though this condition takes a reasonable space of the legal arguments as previously mentioned, it has even become widely used in contracts, such as tenancy, contracting, and financial investments. The study showed that the above-mentioned clause has recently increased its use in financing contracts, especially with the increasing globalization of banking services and bank transfers. Although banks usually prefer to resort to traditional litigation, lack of similarity in the legal rules and judicial applications related to banking transactions and their difference from one country to another was a reason for the banks preference of resorting to arbitration. There is no examination of the legitimacy of an unequal or optional arbitration clause in Bahrain. Also, the Bahraini and Egyptian courts, to the best of our knowledge, did not decide whether it should be considered null or valid. The same case is applied to the French courts which have no cases that examined this type of clauses except for a case in 2006 and the other is a judgment close to the same issue on October 7, 2015, from the French Court of Cassation. The English and American courts were different; they examined this clause and had several judicial implementations due to the fact that most of the arbitration terms are either related to multinational companies operating within the framework of the Wall Street Stock Exchange in New York or those that stipulate the enforcement of British and Wales law on the provisions of the contract . However, many Arab countries, in general, as well as Bahrain and some Gulf countries, in particular, are seeking in their economic model to attract foreign investments and capital, especially those related to financial and banking industries, to diversify sources of income. The decision of investing or not investing the capital in a country is made by the judicial authority in terms of independence as well as the judicial application of legal texts as these factors are directly reflected in the desire to invest and show the possibility of protecting investors.

The Role of the Foreign Cause in the Exemption of the Marine Carrier from Liability in accordance with the Rotterdam Rules: A Comparative legal study - Harb, Mohamed (UAEU Law Journal, 2022)

Settlement of Disputes Arising from Documentary Credit Under National and International Regulations - Nour, Hoda Magdy (UAEU Law Journal, 2022)
The need Settlement of disputes arising from bank credit between national and international rules, protecting the interests of the bank and ensuring its financial rights before the debtor. As the Bank faces different technical and legal difficulties, as well as the multiplicity of legal adaptation, we deal with the rules governing banking accreditation from the point of pleadings law, and the methods of amicable settlement of these disputes and following, and compulsory execution. International efforts are taking the lead in establishing the technical regulation of bank accreditation and setting rules "DOCDEX" in 1997, and the 2015 amendments, which still need more as they do not provide a legal way to implement them. It is necessary to find out legal regulation at the domestic and international levels, which calls for the legislator to intervene to organize its rules and procedures. We have sought in this study to weave the legal entity to seize bank credit within the legally acceptable limits based on a system of seizure of the debtor with third parties against the background of the legal system of documentary credit and the relationships arising from it, and its financial and economic effects that go beyond the parties to the beneficiaries of companies, bodies, and economic institutions, As the matter still requires the existence of special legislation regulating the seizure of bank credit, to ensure the effectiveness of the guarantees surrounding the appropriations by the national legislator and at the international level. This would expand the insurance of bank credit so that the creditors recover their full right directly or by seizing the value of the credit, which calls for organizing this seizure with rules that consider the privacy of this seizure and its rules and are consistent with the required speed in such transactions in a way that protects the creditor from abuse, in a manner that ensures the observance of confidentiality, due process, and the spirit of banking work, anticipate the possible future that will witness the decline of documentary credit and replace it with electronic transactions, the establishment of specialized banking courts that save time and effort.

In-kind Execution of Contractual Obligations: Rule and Exceptions under the UNIDROIT Principles and the French Civil Code - Shandi, Yousef (UAEU Law Journal, 2022)
This research deals with the principle of in kind execution of contractual obligations and the exceptions thereto under the 2016 UNIDROIT Principles and the provisions of the French Civil Code created by decree of 10 February 2016, which amends the Law on Contracts and General Provisions and Proof of Obligations. Both the UNIDROIT Principles and the French civil law establish the principle of in kind execution; it applies to all types of contractual obligations. Nevertheless, the UNIDROIT Principles state five exceptions to this principle, namely: when performance is impossible in law or in fact; when performance is unreasonably burdensome or expensive; when the party entitled to performance may reasonably obtain performance from another source; when performance is of an exclusively personal character; or when the party entitled to performance does not require performance within a reasonable time. Also, the French Civil Code includes similar exceptions to the obligation to perform in kind, namely, if the in kind execution is impossible, and if there is an apparent in proportionality between the cost the good faith debtor would endure and the benefit the creditor would achieve from the in kind execution. This research aims to analyze and compare the provisions on in kind execution under the UNIDROIT Principles and French Civil Law, in order to identify the extent to which they are harmonious or different. Accordingly, the principle of in kind execution of contractual obligations, including the conditions of its application is analyzed in the first chapter. The second chapter tackles the exceptions to this principle, in terms of concept, conditions of application, the judge's authority and the parties’ freedom to exclude them

The Right to Water in Investment Treaty Arbitration and Its Impact on Jurisdiction and Applicable Law - Geravand, Farshad (Public Law Researsh, 2022)
The right to water in investment arbitration has been one of the most contentious issues before investment arbitration tribunals in recent decades. The privatization of public services, including water and sanitation, and assigning them to foreign investors has caused the right to water as a vital benefit being repeatedly raised in investment arbitrations. However, due to tribunals’ narrow interpretation of jurisdiction and applicable law, this fundamental human right has been considered irrelevant and ignored, and this has fueled the legitimacy crises in investment arbitration. This research seeks to indicate the potentiality of more protection of the right to water through balancing the states international obligations in the two areas of investment law and human rights law. Proposed methods for integrating human rights with investment law include the correct interpretation of jurisdictional clauses and the applicable law based on the treaties interpretation principles, systematic integration and the inclusion of new clauses in investment agreements. طرح حق بر آب در داوری سرمایه‌گذاری یکی از مناقشه‌انگیزترین مباحث پیش روی دیوان‌های داوری در چند دهه اخیر بوده است. خصوصی‌سازی خدمات عمومی از جمله آب و فاضلاب و سپردن آنها به سرمایه‌گذاران خارجی موجب شده تا حق بر آب بعنوان یک منفعت عمومی و حیاتی بارها در داوری‌های سرمایه‌گذاری مطرح شود. با تفسیر مضیق محاکم از شروط صلاحیتی و قانون حاکم، این حق بنیادین بشری در برخی موارد نامربوط و نادیده تلقی شده و این امر به بحران مشروعیت در داوری سرمایه‌گذاری دامن زده است. این جستار می‌کوشد تا امکان حمایت بیشتر از حق بر آب را از طریق برقراری تعادل بین تعهدات بین‌المللی دولت‌ها در دو عرصه حقوق سرمایه‌گذاری و حقوق بشر نشان دهد و در پایان روش‌هایی را برای ادغام این دو از جمله تفسیر درست شروط صلاحیتی و قانون حاکم با تکیه بر اصول تفسیر معاهدات، تلفیق سیستمیک و گنجاندن بندهای جدید در موافقتنامه‌های سرمایه‌گذاری پیشنهاد کند.
Keywords: Applicable law; International Investment Arbitration; Jurisdiction; Right to Water; Systemic Integration; تلفیق سیستمیک; حق بر آب; داوری سرمایه‌گذاری بین‌المللی; شروط صلاحیتی; قانون حاکم

التزام العون الاقتصادي بالإعلام عن الأسعار والتعريفات - سكفال, عبد الجليل (مجلة البحوث في الحقوق والعلوم السياسية, 2022)
إن الإعلام بالأسعار والتعريفات التزام قانوني يقع على عاتق البائع من أجل تبصرة المستهلك حتى يكون على علم بما سيقدم له من تعاملات بشكل علني وواضح بهدف إضفاء الشفافية على الممارسات التجارية ، ويتحقق الإعلام بمجموعة من الوسائل العامة وأخرى خاصة نص عليها المشرع الجزائري في القانون 04/02 الذي يحدّد القواعد المطبقة على الممارسة التجارية،كما أن الإخلال بتنفيذ الالتزام بالإعلام يؤدي إلى ترتيب المسؤولية المدنية تتمثل في إمكانية إبطال عقد البيع الاستهلاكي على أساس نظرية عيوب الإرادة أو على أساس عدم العلم الكافي بالمبيع ، وأيضا إقرار المسؤولية الجزائية على كل مخالفي هذا الالتزام بعد إجراء المعاينة وضبط المخالفات من طرف الأشخاص المختصة بالمراقبة وبالتالي توقيع عقوبات جزائية فضلا عن الجزاء الإداري ، هذا من أجل المحافظة على التوازن في العلاقة التعاقدية بين المستهلك باعتباره الطرف الضعيف في العلاقة وبين المتعاملين الاقتصاديين من أجل إرساء أسس النظام العام الاقتصادي. Informing about prices and tariffs is a legal obligation that the seller has in order to inform the consumer so that he is aware of what will be dealt with in a public and clear manner with the aim of imparting transparency to commercial practices The media is verified by a set of public and private means that the Algerian legislator stipulated in law 04-02 witche spicifies the rules aplicable to commercial practice, also the failure to implement the obligation to the media leads to the arrangement of civil liability represented in the possibility of nullifying the consumy sale contract on the basis of theoty of defects of the will or on of the basis of insufficient knowledge of the sale, and also the recognition of criminal liability for all violators of this obligation after conducting the inspection and controlling the violation by the persons concerned whith control consequenlty, penal sanctions are imposed in addition to the administrative penality, in order to maitain balance in the contratctual relationship and the economic dealers in order to lay the foundations of the general economic order.
Keywords: Consumer; Droit de la consommation; Economic aid

الحماية المدنية لقواعد حوكمة الشركات التجارية المتعلقة بمحافظي الحسابات - معمر, خالد; شارف, بن يحي (مجلة البحوث في الحقوق والعلوم السياسية, 2022)
يتضمن هذا البحث الحديث عن موضوع مهم جدا في مسألة حوكمة الشركات التجارية وهو إظهار مواطن التأثير من قبل محافظ الحسابات و إبراز مبادئ الحوكمة وتحقيقها في الشركة التجارية وما يتبعها من وعي لدى أصحاب المصالح وما ينتج عنه من زيادة الثقة في تعاملات الشركة وربحيتها ،لذلك تم الاهتمام بفحص النصوص المنظمة لتعيين محافظي الحسابات وبيان مهامهم ومسؤولياتهم وتقدير كفاية الحماية المدنية التي تحتوي عليها هذه النصوص ومدى ملاءمتها وخدمتها لقواعد الحوكمة. ومن ناحية أخرى حوكمة المسؤولية في حد ذاتها من خلال توقيعها على محافظي الحسابات الذين يستحقون حقا المساءلة وإعفاء من قاموا بواجباتهم التي فرضها القانون على أتم وجه من خلال تكريس القواعد التي تعفي من المسؤولية والأخرى التي تأمنهم منها. This research includes talking about a very important topic in the issue of business governance, which is to show the influence of the portfolios of accounts and to highlight the principles of governance and its realization in the commercial company and the subsequent awareness of stakeholders and the resulting increased confidence in the company's dealings and profitability, so attention was paid to examining the texts governing the appointment of account governors and showing their functions and responsibilities and assessing the adequacy of civil protection contained in these texts and their suitability and service to governance rules. On the other hand, governance of responsibility per se by signing it to the auditors who truly deserve accountability and exempting those who have fully carried out their duties imposed by law by enshrining the rules that exempt them from liability and those from which they are safe.
Keywords: Comptable; Développement; Gouvernance d'entreprise; Responsabilité civile; التنمية; حوكمة الشركات; محافظ الحسابات; مسؤولية مدنية

Role of Abuse of Rights Doctrine and Investment Arbitration Ratione Temporis in Limiting Nationality Planning - Saeedi, Niloofar; Askary, Pouria (Public Law Researsh, 2022)
Sometimes foreign investors after the dispute have arisen or when it is predictable and with the intention of bringing the dispute to arbitration, change their nationality or acquire new nationality. The phenomenon called Nationality Planning eases foreign investors’ access to a desirable treaty and increases the chance of bringing disputes against host states.So host states try to avoid these disputes by raising objections to Ratione Temporis or claiming abuse of rights. Arbitration tribunals’ approach towards their Ratione Temporis and abuse of rights is material in host states’ success in limiting Nationality Planning. So the question to be answered is that what requirements are considered by arbitrations in determining Ratione Temporis and abuse of rights and how these two are different. Arbitral precedent shows that these tribunals make distinction between cases of nationality planning contrary to their Ratione Temporis and cases that are considered as abuse of rights. However, in practice their strict approach results in limited acceptation of objections to Ratione Temporis or abuse of rights claims. گاه سرمایه‌گذار خارجی پس از بروز اختلاف یا زمانی که اختلاف قابل پیش‌بینی است و به قصد طرح دعوی در مرجع داوری، اقدام به تغییر تابعیت یا کسب تابعیت جدید می‌نماید. این اقدام که برنامه‌ریزی تابعیت نام دارد، دسترسی سرمایه‌گذار خارجی به یک معاهده سرمایه‌گذاری مطلوب را تسهیل کرده و احتمال طرح دعوی علیه دولت میزبان را افزایش می‌دهد. از این‌رو دولت‌های میزبان تلاش می‌کنند با طرح ایراد به صلاحیت زمانی یا سوء استفاده از حق، مانع پذیرش چنین دعوایی شوند. رویکرد مراجع داوری در احراز صلاحیت زمانی خود و تشخیص موارد سوء استفاده از حق، در موفقیت یا عدم موفقیت دولت میزبان در مقابله با برنامه‌ریزی تابعیت تعیین‌کننده است. بنابراین باید به این پرسش پرداخته شود که مراجع داوری چه شرایطی را برای احراز صلاحیت زمانی و سوء استفاده از حق در نظر می‌گیرند و چگونه میان این دو تمایز قائل می‌شوند. رویه مراجع داوری حاکی از آن است که این مراجع میان مواردی از برنامه‌ریزی تابعیت که مانع صلاحیت زمانی آن‌هاست و مواردی که سوء استفاده از حق تلقی می‌گردد، تمایز قائل می‌شوند. هرچند رویکرد سخت‌گیرانه آنها در عمل موجب می‌شود تنها در موارد محدودی ایراد به صلاحیت زمانی یا ادعای سوء استفاده از حق مورد پذیرش واقع شود.
Keywords: Abuse of rights; Bilateral Investment Treaty; Foreign Investment Arbitration; Nationality Planning; Ratione Temporis; برنامه‌ریزی تابعیت; داوری سرمایه‌گذاری خارجی; سوء استفاده از حق; صلاحیت زمانی; معاهده دوجانبه سرمایه‌گذاری

Scope of Obligation of the Host State for Protection of Foreign Investor in Armed Conflicts - Shahbazian, Abolghasem; Salimi, Sadegh (Public Law Researsh, 2022)
Measures taken by governments during armed conflict to safeguard their essential interests sometimes cause damages to foreign investors. The investors thus affected seek remedies in the arbitration tribunals invoking breach of host government obligations to protect investments. The host government also usually attempts to assert as defense non-precluded measures to prove its irresponsibility, or if it proves responsible, justify it by resorting to circumstances precluding wrongfulness in the customary international law. But since different courts do not consider the same requirements to invoke these rules, there is no certainty that the parties to the lawsuit will be able to invoke them and, as a result, the scope of government's obligations to protect the foreign investor during the armed conflict is obscure. To clarify the scope of the host government's obligations to protect the foreign investor during armed conflicts and balance the interests of the investor and the host government during the investment disputes arising from the armed conflict, this article explores the possibility and requirements of invoking circumstances precluding wrongfulness and non-precluded measures and the relationship between them. اقداماتی که دولت‌ها در زمان مخاصمات مسلحانه در جهت حفظ منافع اساسی خود انجام می‌دهند گاه موجب ورود خسارت به سرمایه‌گذاران خارجی می‌گردد. سرمایه‌گذاران آسیب‌دیده در محاکم داوری با استناد به نقض تعهدات حمایتی توسط دولت میزبان، خسارات وارده به خود را طلب می‌نمایند. دولت میزبان نیز معمولاً برای اثبات عدم مسئولیت خود به شرط اقدامات منع نشده مندرج در معاهده سرمایه‌گذاری استناد می‌کند و یا در صورت اثبات مسئولیت، به منظور توجیه آن به معاذیر رافع وصف متخلفانه در حقوق بین‌الملل عرفی متوسل می‌شود. اما از آنجا که محاکم مختلف، شرایط یکسانی را جهت استناد کشور میزبان به شرط اقدامات منع نشده و معاذیر رافع وصف متخلفانه در نظر نمی‌گیرند، قطعیتی در امکان استناد به آن‌ها وجود ندارد. در نتیجه، قلمرو تعهد دولت به حمایت از سرمایه‌گذار خارجی در زمان مخاصمات مسلحانه در هاله‌ای از ابهام فرو رفته است. این مقاله با هدف روشن ساختن قلمرو تعهد دولت میزبان به حفاظت از سرمایه‌گذار خارجی در هنگام مخاصمات مسلحانه و به منظور توازن منافع سرمایه‌گذار و دولت میزبان در دعاوی سرمایه‌گذاری ناشی از مخاصمات مسلحانه، امکان و الزامات استناد کشور میزبان به معاذیر عرفی رافع وصف متخلفانه و شرط اقدامات منع نشده و ارتباط میان آنها را مشخص می‌نماید
Keywords: Armed Conflicts; Customary International Law; Foreign investment; Interests of the Host State; Non-Precluded Measures; اقدامات منع نشده; حقوق بین‌الملل عرفی; سرمایه‌گذاری خارجی; مخاصمات مسلحانه; منافع دولت میزبان

Banks responsibility in the collection of the commercial paper contract - Al-Shawabkeh, Wa’ed (Al-Balqa Journal for Research and Studies, 2022)
The importance of studying this contract is to establish the legal nature of the bank’s responsibility when it fails to collect the value of the commercial paper, and to know the role and direction of the judiciary in that respect. The study relied on the element of analysis and education in a brief scientific way. The purpose of the study is to examine the legal basis for the Bank’s responsibility in the collection contract and the general provisions for this responsibility resulting for it, and to cover that responsibility in all its aspects. The study relies on the analytical method in order to achieve the purpose and objectives of the research, where the legal texts will be analyzed and practical results will be reached. In this research legal texts will be analyzed to reach scientific results, the study also reached results, including that there was no regulation from the Jordanian legislator for the collection, in addition to the overlapping of the agency and deposit contracts in the collection contract and that the bank’s responsibility towards its client is a contractual responsibility due to the nature of the relationship between them. The research recommends that the Jordanian Trade law should include special texts dealing with the collection contract, and that the judiciary be more present while evaluating the nature of the relationship and the basis of responsibility between the bank and its client, and it should be clearly stated that the bank may require the disqualification of itself from the liability resulting from collection contract.

Third Party Investment in International Commercial Arbitration - Ebrahimi, Seyed Sadegh; Boloori, Peyman; Solhchi, Mohammad Ali (Public Law Researsh, 2022)
International commercial arbitration imposes heavy costs to the parties involved. In this regard, one of the new phenomena in international commercial arbitration is "financing of court costs by a third party investor. There are several reasons for the emergence of a third party investor: 1- involved parties may not have the resources to pay for the costs of arbitration or they may be reluctant to use their funds to finance the litigation: 2. the uncertainty of receiving compensation as a result of paying the arbitration fees might encourage the parties to transfer this risk to a third party; 3. having its own advantages and disadvantages. Since the funder holds the power of the purse, TPF entails the risk of the control of the claim being transferred to the third party funder. We might ask whether international arbitration tribunals should examine the extent of the investor's influence in determining the allocation of costs or not. In addition, is it essential to disclose the third parties contracts confidential? Overall, it is concluded that those mentioned Tribunals should allocate and guarantee the arbitration cost and agree on disclosing of third parties fund contracts under urgent conditions by international arbitration tribunal. مراجعه به داوری تجاری بین المللی هزینه های کلانی را برای طرفین درگیر در فرآیند داوری به همراه دارد و تأمین این هزینه ها در خیلی از موارد به‌صورت مانع در مراجعه به داوری نمود پیدا می‌کند. در همین راستا یکی از پدیده‌های جدید در داوری تجاری بین المللی، «تأمین مالی هزینه دادرسی توسط سرمایه گذار ثالث» است. ظهور سرمایه گذار ثالث دلایل متعددی دارد؛ اولاً طرفین دعوی ممکن است فاقد امکانات مالی کافی برای هزینه های داوری باشند، ثانیاً ممکن است طرفین دعوی تمایلی به استفاده از منابع مالی خود برای تأمین مالی دادرسی پرهزینه نداشته باشند، ثالثاً عدم قطعیت ذاتی که در زمینه امکان اخذ خسارت در نتیجه دادرسی وجود دارد می تواند باعث تمایل طرف منازعه به انتقال این ریسک به شخص ثالث شود. پرسش این است که آیا محاکم تجاری بین‌المللی تعیین تخصیص هزینه‌ها بپردازد یا خیر؟ و آیا افشاسازی قراردادهای شخص ثالث ضروری می‌باشد؟ در نهایت این نتیجه حاص می‌شود که محاکم مذکور باید به تعیین تخصیص و تضمین هزینه‌های داوری پرداخته و از سویی با افشاسازی قراردادهای تامین مالی شخص ثالث در داوری تجاری بین المللی، در شرایط خاص و ضروری موافقت نمایند.
Keywords: Arbitrage; Arbitragem; Arbitration; Commercial Arbitration; Cost Allocation; Disclosure; International Arbitration Tribunals; International commercial arbitration; Investments; Third Party Investment; Third parties; افشاسازی; تخصیص هزینه‌ها; داوری تجاری بین‌المللی; دیوان‌های داوری بین‌المللی; سرمایه‌گذاری شخص ثالث

A Legal Analysis of the Structure of Dispute Resolution Mechanisms of International Tax Agreements - Salehifar, Alireza (Public Law Researsh, 2022)
As international trade is expanding, international trade and tax disputes are increasing. Under international tax agreements, there are two mechanisms for the resolution of potential disputes between contracting States. These agreements mostly rely on a form of negotiation known as the “Mutual Agreement Process (MAP)” as the main mechanism for the settlement of disputes. During the last decade, the inclusion of “ad hoc arbitration” as a new dispute resolution mechanism in international tax treaties has become popular to augment the MAP. Iran has long concluded several international tax agreements with several countries for the avoidance of double taxation. Due to Iran’s macroeconomic policy for relying more on tax revenues as an alternative to revenues from the petroleum industry, it is important that the Iranian lawyers seek to focus more on tax law and tax dispute resolution mechanisms. The purpose of this article is to introduce and critically analyse the dispute resolution mechanisms of international tax agreements. In this article, to make some suggestions for the improvement of the dispute resolution system of tax treaties, the strengths and weaknesses of the MAP and ad hoc arbitration, will be scrutinised by adopting a descriptive-analytical approach. همسو با گسترش تجارت فراسرزمینی،‌ میزان دعاوی مرتبط با تجارت و مالیات‌های بین‌المللی نیز افزایش یافته است. در بسیاری از معاهده‌های مالیاتی بین‌المللی برای حل اختلافات، دو ساز و کار با عنوان «فرآیند توافق دوجانبه» و «داوری موردی» وجود دارد. فرآیند توافق دوجانبه که مبتنی بر مذاکره بین طرفین معاهده است بعنوان ساز و کار اصلی و داوری موردی هم که در یک دهه اخیر در این معاهده‌ها رواج یافته، بعنوان ساز و کار مکمل فرآیند توافق دوجانبه برای حل اختلافات استفاده می‌شوند. ایران از دیرباز جهت اجتناب از مالیات مضاعف، معاهده‌های مالیاتی متعددی را با کشورهای مختلف منعقد نموده است. همچنین سیاست کلان اقتصادی کشور در سال‌های اخیر مبتنی بر اتکای بیشتر به درآمدهای مالیاتی بعنوان جایگزینی برای درآمدهای نفتی بوده است. لذا اهمیت شناخت این نوع معاهده‌ها و‌ مکانیسم‌های حل و فصل اختلافات آنها برای حقوقدانان کشور بیش از پیش آشکار می‌شود. هدف این مقاله معرفی،‌ تحلیل و نقد ساز و کارهای موجود در معاهده‌های مالیاتی بین‌المللی برای حل اختلافات می‌باشد. در این مقاله نقاط ضعف و قوت فرآیند توافق دوجانبه و داوری موردی به شیوه توصیفی-تحلیلی بیان و راهکارهایی جهت بهبود این مکانیسم‌ها ارائه می‌شود.
Keywords: Arbitrage; Arbitragem; Arbitration; Dispute Resolution; International Tax Agreements; Mutual Agreement Procedure (MAP); Negotiation; داوری; فرآیند توافق دوجانبه; مذاکره; معاهده مالیاتی بین‌المللی; ‌ حل و فصل اختلاف

التضامن الداخلي كنظام إستثنائي ينفرد به قانون الصرف دون غيره من القوانين - بوخاتم, مولياط (مجلة البحوث في الحقوق والعلوم السياسية, 2021)
بالإضافة إلى التضامن الخارجي الذي يربط الموقعين على الورقة التجارية بالحامل، أقام المشرع ضربا من التضامن الداخلي بين الموقعين ببعضهم البعض، فأجاز القانون لكل موقع قام بوفاء قيمة هذه الورقة أن يرجع على مختلف الموقعين منفردين أو مجتمعين بكل ماأوفاه دون أن يتحمل نصيبا معينا متمتعا بجميع الحقوق الناشئة عن هاته الورقة التي كان الحامل السابق يتمتع بها، غير أن هذا الرجوع الذي يقوم به الموفي لايكون إلا على الضامنين السابقين عليه في التوقيع دون اللاحقين المضمونين من طرفه In addition to the external solidarity which binds the signatories of the commercial paper with the holder, the legislator has established a form of internal solidarity between the signatories between them, so that the law allows each site having paid the value of this paper to return to the different signatories individually or collectively with all that they have accomplished without incurring a certain share and enjoying all the rights. Coming out of this paper from which the previous holder benefited, however, this return made by the taxpayer only concerns the guarantors who preceded him in the signature without the following guarantees by him.
Keywords: Committed exchange; External solidarity; Internal solidarity; Morphological return; Morphological solidarity; التضامن الخارجي; التضامن الصرفي; الرجوع الصرفي; الملتزمين الصرفيين

ضمانات الحماية المدنية للمستهلك في التعاقد الالكتروني - باهي, التركي; محمود, حياة (مجلة البحوث في الحقوق والعلوم السياسية, 2021)
ما بين القوة والضعف وجدت الحرية التعاقدية التي كان القانون هو المنقذ لها وهو ما تجسد في الاختيار الحر للمستهلك في العقد الالكتروني الذي تولد نتيجة تطور وسائل الاتصال عبر شبـــكة الانترنت، حيث تغـــيرت أنمـــاط الممــــارسات التجارية وأصبـحت عـقود الاستهــــلاك تتم عــــبر تقنيـــات الكترونية كالهاتــــف الفاكس البـــريد الالكتروني، ومواقع الويب بهدف الحصول على القبول من إيجاب تـلقاه المستهلك عبر إعلانات إلكترونية، و أمام هذا التطور أولت التـشريعات الوطنية والدولية الحديثة اهتماما بالغا بعقد الاســـتهلاك الالكتروني حيث عجزت النظرية العامة للعقد عن حمايــــته مما أدى إلى ظــهور منظومة تشريعية وقائية هدفها تجسيد هــذه الحماية في عقود الاستهلاك في البـيئة الالكترونية. Between strength and weakness, there is contractual freedom, so that the law is its savior and which is embodied in the free choice of the consumer in the electronic contract that was giving birth result by the development of means of communication over the Internet, where the patterns of commercial practices changed and consumption contracts became carried out through electronic technologies such as telephone, fax, e-mail, and web sites via broadcast Free, aiming to gain acceptance from an affidavit received by the consumer via electronic advertisements Faced with this development, national and international modern legislations have paid great attention to the electronic consumption contract, as the general theory of the contract failed to protect it, which led to the emergence of a preventive legislative system aimed at embodying this protection in consumption contracts in the electronic environment

Capacity of the International Investment Arbitration Mechanism in Environmental Protection - Habibi Majandeh, Mohammad; Gholami, Afife (Public Law Researsh, 2021)
Environmental considerations have always been a challenge for foreign investment. The need to observe environmental minimums from the beginning to the end of the investment is also a concern of environmental law activists. In the meantime, the host state faces sometimes conflicting commitments. State dual obligations to foreign investors on the one hand, and the whole citizens on the other, has in many cases led to disputes, rooted in environmental norms. The main question is how the arbitration mechanism can take an active stand in the face of such disputes? The main purpose of this study is to examine the reflection of these conflicts in investment arbitration and the importance and role of arbitration in improving the environmental status. The authors of this paper believe that the arbitration system has tools that it can use in resolving disputes to balance these conflicting obligations. Some of these legal tools are directly or indirectly related to investment agreements, and others are beyond the treaty and based on international principles, rules, customs and practices. ملاحظات محیط زیستی همواره یکی از چالش های پیشروی سرمایه گذاری خارجی بوده است. لزوم رعایت حداقل های زیست‌محیطی از آغاز تا پایان سرمایه گذاری، از دغدغه های فعالان حوزه حقوق محیط زیست نیز می باشد. در این میان دولت میزبان با تعهداتی بعضاً متعارض روبروست. تعهدات دوگانه دولت در برابر سرمایه گذار از یک طرف و عموم شهروندان از طرف دیگر، در موارد متعددی به بروز اختلافاتی منجر شده که ریشه در هنجارهای محیط زیستی دارد. پرسش اصلی این است که سازوکار داوری در مواجهه با این نوع اختلافات، چگونه می تواند فعالانه موضع گیری نمایند؟ هدف اصلی این مطالعه بررسی بازتاب تعارض ها در رویه داوری سرمایه گذاری و اهمیت و نقش داوری در بهبود وضعیت محیط زیستی است. نویسندگان این نوشتار بر این باورند که سیستم داوری، ابزارهایی در اختیار دارد که می تواند از آنها در جریان حل اختلاف برای ایجاد تعادل میان این تعهدات متعارض استفاده کند. برخی از این ابزارهای حقوقی مستقیم یا غیرمستقیم با معاهدات سرمایه‌گذاری مرتبط است و دستهای دیگر فرامعاهده ای و ناشی از اصول، قواعد، عرف ها و رویه های بین المللی است.
Keywords: Arbitrage; Arbitragem; Arbitration; Bilateral Treaties; Environmental Protection; International Arbitration; Investment Disputes; Legal Instruments; ابزار حقوقی; اختلافات سرمایه‌گذاری; حمایت از محیط ‌زیست; داوری بین‌المللی; معاهدات دوجانبه

حكم عقـــد الزواج عبر وسائل الاتصـــال الحديثـــة - دشاش, راضية (مجلة مالك بن نبي للبحوث والدراسات, 2021)
يشهد العالم ثورة رقمية في جميع مجالات الحياة وحركة كبيرة في مجال المعلوماتية ، واستخدام تكنولوجيا الاتصال الحديثة لقدرتها الهائلة في تسهيل عملية نقل وإرسال المعلومات. حيث أصبح التعامل بهذه المخترعات في إبرام العقود المالية والتجارية وحتى الشخصية كعقد الزواج عبر وسائل الاتصال الحديثة الأمر الذي يتطلب نوعا من الحماية والثبات ذلك أن الكثير من الشباب قد يقعون ضحية نصب واحتيال جراء هذا الزواج الأمر الذي يدفع إلى التساؤل عن حكم الزواج عبر وسائل الاتصال الحديثة ؟ وفي حالة حصل ذلك ماهي أهم الوسائل التي يمكن للأطراف الاعتماد عليها لإثبات الزواج عبر وسائل الاتصال ؟ خاصة أنها مسألة مستجدة أصبحت تأثر على الأمن الأسري والاجتماعي وعليه فالقول بجواز الزواج عبر التقنيات المعاصرة لا يعني التوسع فيه وإنما يبقى اللجوء إليه في حالة ظروف لا تسمح للأفراد باللقاء، ومن ثمة تنبيه المشرع الجزائري لهذا الوضع الحساس من خلال النص على عقد الزواج عبر وسائل الاتصال الحديثة في قانون الأسرة وبيان طرق خاصة لإثباته تختلف عن غيرها . The world is witnessing a digital revolution in all areas of life as well as a great movement in the field of informatics, including the use of modern communication technology for its enormous ability to facilitate the process of transmitting and sending information. Dealing with these inventions leads to concluding financial, commercial and even personal contracts, such as the marriage contract through modern means of communication, which requires a kind of protection and stability. As a result, many young people may fall victim to deception, and this make marriage through modern means of communication in question. And if this happens, what are the most important means that the parties can rely on to prove the marriage through modern means of communication? Especially since it is an emerging issue that has affected family and social security, and accordingly, saying that marriage is permissible through contemporary technologies does not mean expanding it, but it remains to resort to it in the case of circumstances that do not allow individuals to meet. Hence, the Algerian legislator alerts this sensitive situation by stipulating the marriage contract through modern means of communication in Family law, showing special different ways to prove it.
Keywords: Communications modernes; Contract; Contrat de mariage; Contrats; Judgment; Jugement; Marriage contract; Modern means of communication; Reporter and electronic signature; Éditeur et signature électroniques; التعاقد; الحكم; المحرر والتوقيع الالكتروني; عقد الزواج; وسائل الاتصال الحديثة

ضوابط إبرام الإتفاقيات بين شركة المساهمة والقائمين بإدارتها - العابد, توفيق; بوساحة, نجاة (Revue des Sciences Juridiques et Politiques, 2021)
يُسلِط هذا المقال الضوء على الضوابط التي تضمنها القانون التجاري الجزائري، في مجال إبرام الاتفاقيات بين شركة المساهمة والقائمين بإدارتها، بغية التوصل إلى معرفة مدى نجاعتها في ضمان حماية الشركة من العواقب الناجمة عن تعارض المصالح، وذلك من خلال التعرض بالوصف والتحليل للصور والإجراءات التي أقرتها النصوص القانونية الناظمة، بالإضافة إلى ما تم اعتماده في بعض التشريعات المقارنة. وقد خلصت الدراسة إلى أن المشرع الجزائري لم يحقق توازناً فعلياً بين سلطتي الإدارة والرقابة، نظرا لاعتماده على المراقبة البعدية التي أثبتت التجارب العملية عدم فعاليتها في معالجة قصور نظرية الوكالة. The article sheds light on the regulations of making agreements between the joint-stock company and its administrators in Algerian commercial law. In order to find out their effectiveness in ensuring that the company is protected from the consequences of conflicting interests, the images and procedures which are approved by the legal texts and have been adopted by comparative legislation were described and analyzed. The study concluded that the Algerian legislator did not achieve an effective balance between the authority of administration and that of censorship, due to the reliance on posteriori control, which practical experiences have proven ineffective in addressing the deficiencies of the agency theory.
Keywords: Administrators; Agreements; Conflicting interests; Joint-stock company; Regulations

The effects of fraud by the beneficiary of the letter of guaranty on the obligation of the bank according to UNICITRAL 1995: a comparative study - Mustafa, Hamdi (UAEU Law Journal, 2021)
The research focuses on the effect of fraud of the beneficiary of the international letters of guarantee on the international commitment of the bank through UNICITRAL rules for 1995. Article 19 of UNCITRAL illustrates the cases where the guarantor is able to waive the payment to the beneficiary. UNICITRAL rules grant the bank the power to refuse payment when the claim of the client is supported by fake documents and so it keeps the balance between the different interests. UNICITRAL rules grant the bank the discretionary authority of the payment. The bank's role to maintain the confidence in the letter of guarantee and the characteristics of the letter of guaranty, which is independent and separate from the bank’s obligation towards the beneficiary of the letter of guaranty, is taken into account. In addition to that, these rules affirm the right of the client to take temporary judicial proceedings in the cases of exception from the payment in accordance with Article 19 of UNCITRAL. My research is divided into two sections, the first section is on the concept of fraud, its provisions and conditions according to UNICITRAL and the second section highlights the effects of the fraud on the bank’s commitment and means to protect its client. I have discussed the rules of international conventions of fraud and abuse of the authority by the beneficiary of the letter of guaranty before and after 1995. Finally, I referred to the beneficiary fraud in the Egyptian legislation

The Relationship between International and Domestic Law in the Field of Attribution of Responsibility to a State in International Investment Disputes - Amidimehr, Elham; Seifi, Jamal (Public Law Researsh, 2021)
The attributability of actions to states within the context of investment treaty disputes and to focus on the roles played by international and domestic laws in such attributions have caught the attention of jurists in recent years. The ILC Draft Articles on Responsibility of States for Internationally Wrongful Acts, and particularly, article 3 points to the main outcome of this debate, where it does not consider domestic law irrelevant in internationally wrongful acts and stipulates that the issue is subject to international law and it will take into account the relevance of domestic law. Thus, although the characterization of an act of a State as internationally wrongful is an independent function of international law and such characterization is not affected by the characterization of the same act as lawful by domestic law, it does not mean that domestic law is irrelevant to such description; on the contrary, it may be related in various ways. The present article attempts to examine the challenging junction of domestic and international law with regard to the attributability of actions taken within the framework of investment treaties, specifically by state-owned and para-statal entities that exercise elements of state authority. قابلیت انتساب عمل به دولت در چارچوب اختلافات معاهده‌ سرمایه‌گذاری و تمرکز بر نقش‌هایی که حقوق بین‌الملل و حقوق داخلی در چنین انتسابی ایفا ‌می‌نمایند در زمره‌ مباحثی است که در سال‌های اخیر بسیار مورد ‌توجه حقوقدانان بوده و ماده 3 مواد کمیسیون حقوق بین‌الملل در ارتباط با مسئولیت دولت‌ها نیز بیانگر پیامد اصلی این بحث است که فی‌الواقع، حقوق داخلی را با مسأله متخلفانه بودن اعمال از حیث بین‌المللی بی‌ارتباط تلقی ‌ننموده، بلکه مقرر ‌می‌دارد مسئله مورد بحث، تابع حقوق بین‌الملل است لیکن حقوق بین‌الملل نیز خود تا حدِ ارتباط، حقوق داخلی را در نظر خواهد گرفت. بنابراین اگرچه توصیف خصوصیات یک عمل به عنوان عملی غیرقانونی از عملکردهای مستقل حقوق بین‌الملل است که تحت ‌تأثیر توصیف خصوصیات این عمل بموجب حقوق داخلی قرار نمی‌گیرد لیکن این گفته بدین معنی نیست که حقوق داخلی با توصیف عمل متخلفانه‌ بین‌المللی بی‌ارتباط ‌است؛ بالعکس، ممکن ‌است به طرق مختلفی به آن مرتبط‌ باشد. در این مقاله سعی بر‌ آن است که تلاقی چالش‌برانگیز حقوق داخلی و حقوق بین‌الملل در بحث قابلیت انتساب اعمال ‌صورت ‌گرفته در چارچوب معاهدات سرمایه‌گذاری توسط ارگان‌های دولتی و نهادهای نیمه‌دولتی که عناصر اختیارات دولتی را اعمال می‌نمایند مورد واکاوی قرار‌ گیرد.
Keywords: Attribution; Domestic Law; International Arbitration; International Investment Treaties; International Law; حقوق بین‌الملل; حقوق داخلی; داوری بین‌المللی; معاهدات سرمایه‌گذاری بین‌المللی; کلیدواژگان انتساب مسئولیت

A Reflection on the Invalidation of Patents in the Light of Constituent Elements of Indirect Expropriation under Foreign Investment Law - Rahbari, Ebrahim; Shahabi, Mahdi; Falahati, Soroosh (Public Law Researsh, 2021)
Patents are considered as investments protected under the International Investment Law. Although, these properties are protected under the principle of territoriality, similar to other investments, they can be expropriated as a result of host states’ regulatory measures inconsistent with protection standards stemming from foreign investment protection regulations and treaties including fair and equitable treatment and legitimate expectations of foreign investors. Considering the fact that few arbitration awards have been issued by arbitration panels in this regard, it is yet difficult to claim there is a strong precedent in International Investment Law. Nevertheless, reflecting the provisions of international regulations, the stance of the domestic law and the most important relevant case, this article provides the most significant elements of indirect expropriation as well as existing doctrines in this respect and further investigates whether invalidation of patents can amount to indirect expropriation. It will also be mentioned that despite the fact that according to several foreign investment protection treaties, invalidation of patents shall not be subject to regulations regarding indirect or creeping expropriation, the final determination lies with the arbitration panel. یکی از مصادیق سرمایه‌گذاری خارجی مورد حمایت در حقوق بین‌الملل سرمایه‌گذاری، اختراعات است. این دسته از دارایی‌ها علی‌رغم به رسمیت شناخته شدن در پرتو اصل سرزمینی بودن حمایت، همانند سایر سرمایه‌گذاری‌ها می‌توانند تحت تدابیر حاکمیتی دول میزبان که مغایر با استانداردهای حمایتی نشأت گرفته از قوانین و معاهدات بین‌المللی حمایت از سرمایه‌گذاری خارجی همچون شرط رفتار عادلانه و منصفانه و صیانت از انتظارات مشروع و معقول سرمایه‌گذار می‌باشند، با خطراتی همچون سلب مالکیت مواجه شوند. نظر به صدور آرای معدود مراجع بین‌المللی در این خصوص، سخن گفتن از شکل‌گیری رویه‌ای متقن در این راستا دشوار می‌باشد. با این حال، در این نوشتار ضمن بررسی مهمترین عناصر متشکله سلب مالکیت غیرمستقیم و دکترین‌های موجود در این زمینه، به بررسی قابلیت تطبیق ابطال گواهی ثبت اختراع با سلب مالکیت غیرمستقیم پرداخته و با تشریح مقررات برخی اسناد بین‌المللی، موضع حقوق داخلی و مهم‌ترین پرونده مربوط به این موضوع در حقوق سرمایه‌گذاری خارجی در ابعاد گوناگون آن مداقه نموده و در نهایت به این نتیجه خواهیم رسید که حتی در صورت مستثنی نمودن ابطال گواهی ثبت اختراع از مقررات مربوط به سلب مالکیت در معاهدات حمایت از سرمایه‌گذاری خارجی، تشخیص نهایی تحقق سلب مالکیت با دیوان داوری است.
Keywords: Elements of indirect expropriation; Foreign investment; Indirect expropriation; Intellectual property; Invalidation of patents; ابطال گواهی ثبت اختراع; حقوق مالکیت فکری; سرمایه‌گذاری خارجی; سلب مالکیت غیرمستقیم; عناصر سلب مالکیت غیرمستقیم

The Ability of Short-term Accounting Accruals to Predict Cash Flows of Algerian Companies - Bilal, Kimouche (An-Najah University Journal for Research - B (Humanities), 2020)
هدفت الدراسة إلى استكشاف مدى قدرة المستحقات المحاسبية قصيرة األجل على التنبؤ بالتدفقات النقدية، حيث شملت 14 شركة جزائرية بين 2003 و،2015 ليبلغ عدد المشاهدات الكلية خالل الفترة 117 مشاهدة. وقد تم قياس التدفقات النقدية بصافي التدفقات النقدية التشغيلية، وتم التعبير عن المستحقات المحاسبية قصيرة األجل بـ: التغير في حسابات الزبائن والمدينين، التغير في حسابات الموردين والدائنين، والتغير في المخزونات. وقد أثبتت النتائج ضعف قدرة المستحقات المحاسبية قصيرة األجل على التنبؤ بالتدفقات النقدية للفترة المقبلة، حيث كانت عالقة هذه األخيرة ببنود المستحقات المحاسبية قصيرة األجل غير معنوية، باستثناء عالقتها بالتغير في حسابات الموردين والدائنين This study aims to explore the ability of short-term accounting accruals to predict cash flows. It included 117 observations during 2003 to 2015, which concern 14 Algerian companies. Cash flows have been measured by operating cash flow (OCF). However, short-term accounting accruals have been expressed by change of accounts receivable and debtors, change of accounts payable and creditors, and change of inventories. The results indicated a failure of current short-term accounting accruals to predict cash flows of next period. Except for change of accounts receivable and debtors, the correlations of future operating cash flows with other Short-term accounting accrual items are not significant.
Keywords: Cash flows; Change of accounts payable and creditors; Change of accounts receivable and debtors; Change of inventories; Long-term accounting accruals; Short-term accounting accruals

Increasing participation as a model for the management of Islamic insurance: Parties form and means of operation and success - Abu-mounes, Raed (An-Najah University Journal for Research - B (Humanities), 2020)
This study deals with a statement the parties to form in the framework of increased participation in Islamic Insurance Company, and describes the types of claimants of the company to fulfill its obligations, as well as providing a detailed mechanism on how to manage the Islamic Insurance Company through the increasing capital participation model, which is represented through a common portfolio that combines the capital of both the shareholders and the policyholders, this model represents the Islamic Insurance Company asa capital-based company, where the policyholders have the ability to increase their shares.This model will satisfy the different needs and wants of customers of the Islamic insurance company.And in order to achieve these goals, the study illustrated themain operations of the Islamic insurance company through five offices of operation: the first office: Reception Customer Service and being decades increasingly involved with the campaign documents,SecondOffice: operations management, which are contractsfor trade-offs with service providers on one hand, and the beneficiaries of Islamic insurance in all sectors on the other hand, Third Office: Accounting Department of Interior, which manages the contracts of partnerships with service providers, The fourth Office: Management of exit and liquidation, which regulates contracts trade-offs with the beneficiaries of insurance, and the fifth Office: Management of audit and control, together with the benchmarks to help the success of the application form to participate in the growing Islamic insurance company.This study has concluded that founding the relationship between the policyholders and the Islamic insurance company on the basis of a capital-based company, where the company management is employed for the purpose ofinvesting the company assets, In exchange for a return, in a way that achieves the goals of both the Islamic insurance company and thegoals of thepolicyholders. This foundation is concluded to be the optimal Islamic module, for it achievesIslamiccredibility and economic efficiency, as well as achieving harmony between the intents of the policyholders and the shareholders in the Islamic insurance company.

اختيار الطرفين "قواعد قانونية" للتطبيق على العقد التجاري الدولي أمام المحاكم الوطنية - Dawwas, Amin (Journal of the Arab American University, 2020)
وفقا لقاعدة اإلسناد في عديد من الدول العربية، يسري على العقد التجاري الدولي القانون الذي اختاره الطرفان. ووفقا للقضاء الدارج والفقه الغالب بنبغي أن يكون هذا القانون المختار لحكم العقد قانون دولة معينة. أما في حال إذا ما اختار الطرفان "قواعد قانونية"، فال يتم عادة االعتراف بها كقانون يحكم العقد، وإنما يؤخذ بها في أحسن األحوال على أنها جزء من بنود العقد، وبما ال يتعارض مع النصوص اآلمرة في القانون الواجب تطبيقه على العقد. وعلى الساحة التجارية الدولية، فقد صدرت مبادئ الينيدروا لعقود التجارة الدولية )بصيغتها األخيرة للعام 2016( ) UNIDROIT 2016 Principles)، والتي تعد مثاال جيدا للقواعد القانونية الممكن اختيارها للتطبيق على العقد. وكذلك، فقد صدرت عام 2015 مبادئ الهاي الختيار القانون المنطبق على العقود التجارية الدولية، والتي تسمح في مادتها )3( بأن يختار الطرفان "قواعد قانونية" لحكم العقد. يهدف هذا البحث إلى بيان إمكانية أن يعترف القضاء، ال سيما في الدول العربية، باختيار الطرفين قواعد قانونية، كمبادئ الينيدروا )Principles UNIDROIT) مثال، لحكم عقدهما التجاري الدولي According to the conflict-of-laws rule in many Arab countries, the international commercial contract is subject to the law chosen by the parties. According to the prevailing opinion in judiciary and doctrine, the law chosen by the parties to govern the contract should be a law of a particular State. If the parties chose "rules of law", such a choice will generally not be recognized as the law governing the contract. Rather, courts would consider such a choice as an incorporation of the rules of law into the contract, provided that such chosen rules of law shall not contradict the mandatory rules of the law applicable to the contract. At the international level, in 2016, Unidroit published the latest version of its Principles on International Commercial Contracts. These Principles form a good set of rules of law that can be chosen to govern the contract. In 2015, The Hague Principles on Choice of Law in International Commercial Contracts were also published. Article 3 thereof explicitly enables the parties to choose rules of law to govern the contract. This research aims to indicate the possibility that the judiciary, particularly in the Arabic States, recognizes the rules of law chosen by the parties (e.g. the Unidroit Principles on International Commercial Contracts) as the law applicable to the contract.
Keywords: Choice by the Parties of Rules of Law; Hague Principles; International commercial contracts; Law Applicable; Private International Law; UNIDROIT Principles

التحكيم رديفاً للقضاء في حل المنازعات - دراسة فقهية - Abu Lail, Mohammad (Jordan Journal of Islamic Studies, 2020)
Arbitration is considered as one of the basic means that has been legislated by Islam to resolve the people's disputes. Usually the resolutions of the arbitration are fast, guarantee the rights, respect the essence of justice and reduce the level of the controversy. Today, arbitration plays a vital role in resolving the international disputes such as the economic, political and local disputes as long as its effect upon the resolution of the internal disputes. This study highlights on the arbitration role in resolving the disputes as along with judiciary through showing the advantages of the arbitration and explain the relationship between arbitration and judiciary. And clarify its areas and its implications in jurisprudence. This study found out that the arbitration has a pivotal role in resolving the disputes resulting from the contractual and non-contractual relationships and the disputes resulting from the people in their natural and moral capacity, both internally as well as externally The study has shown the jurisprudence has taken the lead in explaining the terms and effects of the arbitration.

التنظيم القانوني للإيداع وأثره في حماية الأعمال الفكرية والفنية - سماحي, أنس; بومسلة, عبد القادر (مجلة الفقه القانوني والسياسي, 2019)
بعد بدايات بروز الحماية القانونية للحق الفكري في القرون الوسطى كان لابد من ايجاد الوسائل والتنظيمات القانونية لجمع هذه الاعمال الفكرية بمعية جهاز متخصص لحفظها ووقايتها لما تكوَنه من التراث الثقافي الوطني، فقد ظهرت عدة أنظمة لإيداع الأعمال الفكرية على اختلاف اعتباراتها، فمنها من نظر إليها كوسيلة للحماية والمحافظة وحصر العمل الفكري، ومنها من اعتبرها كشرط للحصول على الأرباح التجارية أو بصورة أخرى كإجراء ضروري من أجل عرضها على الجمهور، وتماشيا مع ذلك بدأت القوانين الدولية والوطنية في تنظيم هذه المسائل التي تؤطر إجراءات الإيداع وحماية الأعمال الفكرية. سار النظام التشريعي في الجزائري على غرار باقي التشريعات لتنظيم عملية الايداع القانوني للأعمال الفكرية حيث يرجع بدايات العمل بنظام الإيداع في الجزائر للقوانين الموجودة في فرنسا وتطبيقها في الجزائر فنظمت عملية الايداع بموجب أوامر الجنرال كافينياك في 13 مارس 1848و استمر العمل بنظام الإيداع القانوني على جملة من القوانين الفرنسية إلى غاية سنة 1996 أين تم إقرار قانون الإيداع الوطني الجزائري بموجب الأمر رقم 96-16 مؤرخ في 02 يوليو 1996 لوضع حد للتجاوزات والانتهاكات للموروث الفكري الوطني. After the beginnings of the Legal protection of intellectual right in the Middle Ages, that make it necessary to find the means and legal regulations to collect these intellectual works, With a specialized apparatus To save and protect them, As it forms a national cultural heritage. There have been several systems for filing intellectual works of different considerations, some of them viewed it as a means of protection, preservation and confinement of intellectual work, and some consider it a condition for commercial profit or otherwise necessary for public viewing, In line with this, the international and national laws have begun to regulate these issues, which frame deposit procedures and the protection of intellectual work. The legislative system in Algeria and the others legislations regulate the legal deposit of intellectual works, so the introduction of the deposit system in Algeria is due to the laws in France and their application in Algeria, the deposit was organized by General Caviniac's orders on March 13, 1848, that the legal deposit system continued on a number of French laws until 1996, the Algerian National Deposit Act was adopted by Order No. 96-16 dated 02 July 1996, to end abuses and violations of the national intellectual heritage.
Legal regulation of deposit and the impact of the protection of intellectual and artistic works
Keywords: Deposit; Intellectual property; Patrimoine artistique; Propriedade intelectual; Propriété artistique; Propriété intellectuelle; Propriété littéraire; الايداع; التراث; الفني; الموروث

Immunity from seizure of public properties in Iran: A critical and comparative Approach - طوق, مسلم آقایی; Lotfi, Hasan (Faṣlnāmah-i Pizhūhish-i Huqūq-i ̒Umūmī, 2017)
الف) فارسی کتابها - پاهکیده، امین، (1392)، تشریفات ویژه رسیدگی به دعاوی دولت در آیین دادرسی مدنی ایران، تهران: جنگل. - رفیعی، علی، (1390)، اجرای احکام مدنی علیه دولت، تهران: فکرسازان. - شهری، غلامرضا، (1393)، حقوق ثبت اسناد و املاک، چاپ چهلم، تهران: جهاد دانشگاهی. - طباطبایی مؤتمنی، منوچهر، (1390)، حقوق اداری، چاپ شانزدهم، تهران: سمت. - مردانی، نادر و محمد قهرمان، (1390)، اجرای احکام مدنی و احکام و اسناد لازم‌الاجرای خارجی در ایران، تهران: میزان. - مهاجری، علی، (1392)، شرح جامع قانون اجرای احکام مدنی، جلد اول، چاپ هفتم، تهران: فکرسازان. مقالهها - رستمی، ولی و کیومرث سپهری، (1389)، «اجرای احکام مدنی علیه اشخاص حقوقی حقوق عمومی؛ موانع و راهکارها»، حقوق، دوره 40، شماره 2. - مردانی، نادر و محمدمجتبی رودی جانی، (1385)، «استثنائات وارده بر توقیف اموال در قانون اجرای احکام مدنی»، مجله کانون وکلا، شماره 192 و 193. ب) فرانسوی کتابها
Titre en français : Immunité contre la saisie de biens publics en Iran : une approche critique et comparative
Keywords: Droit administratif; Droit comparé; Immunité; Propriété gouvernementale; Propriété publique; Saisie; Services publics